Feature ranking of type 1 diabetes susceptibility genes improves prediction of type 1 diabetes - Winkler, Christiane; Krumsiek, Jan; Buettner, Florian; Angermueller, Christof; Giannopoulou, Eleni Z.; Theis, Fabian J.; Ziegler, Anette-Gabriele; Bonifacio, Ezio (Diabetologia, 2014)
Aims/hypothesis More than 40 regions of the human genome confer susceptibility for type 1 diabetes and could be used to establish population screening strategies. The aim of our study was to identify weighted sets of SNP combinations for type 1 diabetes prediction. Electronic supplementary material The online version of this article (doi:10.1007/s00125-014-3362-1) contains peer-reviewed but unedited supplementary material, which is available to authorised users. Methods We applied multivariable logistic regression and Bayesian feature selection to the Type 1 Diabetes Genetics Consortium (T1DGC) dataset with genotyping of HLA plus 40 SNPs within other type 1 diabetes-associated gene regions in 4,574 cases and 1,207 controls. We tested the weighted models in an independent validation set (765 cases, 423 controls), and assessed their performance in 1,772 prospectively followed children. Results The inclusion of 40 non-HLA gene SNPs significantly improved the prediction of type 1 diabetes over that provided by HLA alone (p=3.1×10-25), with a receiver operating characteristic AUC of 0.87 in the T1DGC set, and 0.84 in the validation set. Feature selection identified HLA plus nine SNPs from the PTPN22, INS, IL2RA, ERBB3, ORMDL3, BACH2, IL27, GLIS3 and RNLS genes that could achieve similar prediction accuracy as the total SNP set. Application of this ten SNP model to prospectively followed children was able to improve risk stratification over that achieved by HLA genotype alone. Conclusions We provided a weighted risk model with selected SNPs that could be considered for recruitment of infants into studies of early type 1 diabetes natural history or appropriately safe prevention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Type 1 diabetes; Type 1 diabetes susceptibility genes